ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN THE TEACHING OF SOCIAL AND HUMANITARIAN SCIENCES - Ergashev Ibodulla (Modern American Journals, 2025)
This article examines the theoretical and practical aspects of using artificial intelligence technologies in teaching social and humanitarian sciences. It highlights the significant role of AI tools in personalizing the learning process, increasing educational efficiency, and fostering students’ creativity and critical thinking skills. The study also explores the advantages of AI-based learning platforms, automated analytical systems, and interactive instructional models, offering innovative solutions to contemporary pedagogical challenges.
Keywords: Artificial intelligence, digital education, innovative pedagogy, social and humanitarian sciences, educational technologies, interactive learning, distance education, digitalization.